Accounting for the sale of goods through the marketplace ("Journal "U". Economy. Management. Finance.", 2023)
The article is devoted to the analysis of the peculiarities of accounting when selling goods through electronic trading platforms. The paper considers the categories of organizations that have the right to work with marketplaces, lists the key elements of the organization of accounting in this area, shows the correspondence of accounting accounts for transactions through the marketplace, notes the main errors in the work of the accountant who keeps records of sales through the marketplace.
Keywords: accounting; marketplace; accountant; tax accounting; agency agreement; electronic document management; seller; goods; accounting accounts; online sales register